Jaime Balmes on phrenology: A dialogue between faith and science - Aonso Diego, Juan Carlos (Razón y fe, 2023)
In 1843, a debate arose between the theologian Jaime Balmes and the phrenologist Mariano Cubí. The former questioned the scientific bases of the recent science of skull measuring and its illegitimate incursions in other fields of knowledge. The debate is an early example of the dialogue between science and theology in the 19th Century Spain.